A Climbing (Bouldering) Intervention to Increase the Psychological Well-Being of Adolescents in the Bekaa Valley in Lebanon-Study Protocol for a Controlled Trial - Luttenberger, Katharina; Najem, Charbel; Rosenbaum, Simon; Sifri, Charles; Kind, Leona; Baggenstos, Beat (International Journal of Environmental Research and Public Health, 2023)
(1) Background: Adolescent refugees in Lebanon and Lebanese youth are both at high risk of suffering from reduced psychological well-being. Sport is an evidence-based strategy for improving mental and physical health, and climbing is a type of sport that may positively impact both. The aim of this study is to test the effect of a manualized, psychosocial group climbing intervention on the well-being, distress, self-efficacy, and social cohesion of adolescents in Lebanon. In addition, the mechanisms behind psychological changes will be investigated. (2) Methods: In this mixed-methods waitlist-controlled study, we are allocating a minimum of 160 participants to an intervention (IG) or a control group (CG). The primary outcome is overall mental well-being (WEMWBS) after the 8-week intervention. Secondary outcomes include distress symptoms (K-6 Distress Scale), self-efficacy (General Self-Efficacy Scale; GSE), and social cohesion. Potential mechanisms of change and implementation factors are being investigated through qualitative interviews with a subgroup of 40 IG participants. (3) Conclusions: The results may contribute to knowledge of sports interventions and their effects on psychological well-being and will provide insights regarding low-intensity interventions for supporting adolescent refugees and host populations in conflict-affected settings. The study was prospectively registered at the ISRCTN platform (current-controlled trials). ISRCTN13005983.
CRIS-Team Scopus Importer:2023-03-24
Keywords: adolescent mental health; bouldering/climbing; intervention studies; physical activity; refugees

Bouldering psychotherapy is not inferior to cognitive behavioural therapy in the group treatment of depression: A randomized controlled trial - Luttenberger, Katharina; Berking, Matthias; Kind, Leona; Weiss, Maren; Kornhuber, Johannes; Dorscht, Lisa; Karg-Hefner, Nina (British Journal of Clinical Psychology, 2021)
Objectives: Bouldering has shown promising results in the treatment of various health problems. In previous research, bouldering psychotherapy (BPT) was shown to be superior to a waitlist control group and to physical exercise with regard to reducing symptoms of depression. The primary aim of this study was to compare group BPT with group cognitive behavioural psychotherapy (CBT) to test the hypothesis that BPT would be equally as effective as CBT. Design: We conducted a randomized, controlled, assessor-blinded non-inferiority trial in which 156 outpatients meeting the criteria of a depressive episode according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) were randomly assigned to one of the two intervention groups (CBT: N = 77, BPT: N = 79). Methods: Intervention groups were manualized and treated for 10 weeks with a maximum of 11 participants and two therapists. The primary outcome was depressive symptom severity assessed with the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Patient Health questionnaire (PHQ-9) at the beginning and end of the treatment phase as well as one year after the end of treatment. Result: In both groups, depressive symptoms improved significantly by an average of one severity level, moving from moderate to mild depressive symptoms after therapy (MADRS difference scores: BPT −8.06, 95% CI [−10.85, −5.27], p <.001; CBT −5.99, 95% CI [−8.55, −3.44], p <.001). The non-inferiority of BPT in comparison with CBT was established on the basis of the lower bound of the 95% confidence interval falling above all of the predefined margins. BPT was found to be effective in both the short (d = 0.89) and long term (d = 1.15). Conclusion: Group BPT was found to be equally as effective as group CBT. Positive effects were maintained until at least 12 months after the end of therapy. Thus, BPT is a promising approach for broadening the therapeutic field of therapies for depression. Practitioner points: Physical activity is effective in the treatment of depression and current guidelines explicitly recommend it as a complementary method for the treatment of depression. Nevertheless, body-related interventions are still underrepresented in current treatments for depression. Bouldering psychotherapy (BPT) combines physical activity with psychotherapeutic content. Its concept relies on proven effective factors from CBT such as exposure training, problem solving and practicing new functional behaviours and is thus an enrichment and implementation of CBT methods on the bouldering wall. The positive effect of group bouldering psychotherapy (BPT) in reducing depressive symptoms in outpatients with depression is not inferior to the effect of group cognitive behavioural therapy (CBT). Additionally the 10-weeks BPT-programme significantly improved symptoms of anxiety and interpersonal sensitivity as well as health-related quality of life, coping, body image, self-efficacy, and global self-esteem.
Created from Fastlane, Scopus look-up
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; Group; physical activity; psychotherapy; rock climbing; sports

New ways to cope with depression—study protocol for a randomized controlled mixed methods trial of bouldering psychotherapy (BPT) and mental model therapy (MMT) - Kind, Leona; Luttenberger, Katharina; Leßmann, Vivien; Dorscht, Lisa; Mühle, Christiane; Müller, Christian P.; Siegmann, Eva-Maria; Schneider, Sophia; Kornhuber, Johannes (Trials, 2023)
Background: Due to the growing gap between the demand and supply of therapeutic services for people suffering from depression, with this study, we are investigating the effectiveness and factors of influence of new approaches in group treatments for depression. Two previous studies have already identified bouldering psychotherapy (BPT) as an effective option. It combines psychotherapeutic interventions with action- and body-oriented bouldering exercises. Mental model therapy (MMT) is a new cognitive-behavioral approach for treating depression. It focuses on identifying cognitive distortions, biases in decision making, and false assumptions and aims to correct and replace them with useful mental models. We aim to investigate the effectiveness of the interventions compared with a control group (CG) and to assess the factors of influence in a mixed methods approach. Methods: The study is being conducted as a randomized controlled intervention trial. Adult participants with unipolar depression are being randomized into three groups (BPT, MMT, or CG), and the first two groups are undergoing a 10-week treatment phase. CG follows their individual standard treatment as usual. A priori power analysis revealed that about 120 people should be included to capture a moderate effect. The primary outcome of the study is depression rated with the Montgomery and Asberg Depression Rating Scale (MADRS) before (t0), directly after (t1), and 12 months after the intervention phase (t2). Data are being collected via questionnaires, computer-assisted video interviews, and physical examinations. The primary hypotheses will be statistically analyzed by mixed model ANOVAs to compare the three groups over time. For secondary outcomes, further multivariate methods (e.g., mixed model ANOVAs and regression analyses) will be conducted. Qualitative data will be evaluated on the basis of the qualitative thematic analysis. Discussion: This study is investigating psychological and physical effects of BPT and MMT and its factors of influence on outpatients suffering from depression compared with a CG in a highly naturalistic design. The study could therefore provide insight into the modes of action of group therapy for depression and help to establish new short-term group treatments. Methodological limitations of the study might be the clinical heterogeneity of the sample and confounding effects due to simultaneous individual psychotherapy. Trial registration: ISRCTN, ISRCTN12347878. Registered 28 March 2022, https://www.isrctn.com/ISRCTN12347878 .
CRIS-Team Scopus Importer:2023-09-29
Keywords: Biomarkers; Bouldering; Depression; Exercise; Factors of influence; Mental models; Osteocalcin; Psychotherapy; Rock climbing; Sports

Treating depression in an outpatient setting: Predictors of patient response to bouldering psychotherapy, cognitive behavioural therapy or exercise alone - Luttenberger, Katharina; Donath, Carolin; Grässel, Elmar; Kornhuber, Johannes; Schlüter, Annika; Dorscht, Lisa; Kind, Leona (Clinical Psychology & Psychotherapy, 2023)
Background: Bouldering psychotherapy (BPT) for depression has proven effective, but nothing is known about its potential predictors of response. This study should identify predictors of response to BPT, cognitive behavioural therapy (CBT) and an active control (home-based exercise programme; EP) using a literature-based model. Methods: In a multicentre randomised controlled trial, 233 outpatients were assigned to BPT, CBT or EP. Response (reduction of at least 46% on the Montgomery–Åsberg Depression Rating Scale [MADRS]) and remission (≤7 MADRS points) were defined as suggested by the literature. Predictors of response were identified twofold: (1) univariate analyses followed by logistic regression analyses in each group with all predictors yielding a univariate p-value <.20 and (2) a backward regression analysis with all potential predictors. Only variables that emerged as predictors in both types of analyses were interpreted. Results: There was a significantly greater proportion of responders (p =.035) in the BPT than in the EP. The chance of response in the BPT was higher for patients with a higher health-related quality of life. In the EP, response was higher for patients with lower interpersonal sensitivity, suffering from their first episode and living with a partner. Conclusions: Response rates in BPT are similar to or even higher than in other outpatient psychotherapy group therapies. BPT and CBT are suitable for a wide range of patients, but patients with higher functionality could start with psychoeducation and exercise.
CRIS-Team Scopus Importer:2023-09-15
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; group psychotherapy; psychotherapy

Validation of the German version of the state mindfulness scale for physical activity in a clinical sample - Wallner, Jan; Kind, Leona; Donath, Carolin; Kornhuber, Johannes; Luttenberger, Katharina (Journal of Patient-Reported Outcomes, 2024)
Background: Mindfulness has been studied as a treatment option for a large range of psychological disorders and is associated with a multitude of positive psychological outcomes. There are now several scales for measuring mindfulness as both a trait and a state. As mindfulness potentially plays a critical role in maintaining physical activity habits, the State Mindfulness Scale for Physical Activity (SMS-PA) was developed to specifically measure mindfulness in a physical activity context. This study aimed to provide validity evidence for a German version of the SMS-PA (henceforth called SMS-PA-G) in a clinical sample. Methods: We used baseline data from 129 participants in the randomised controlled trial ‘New Ways to Cope with Depression’. The sample, which was screened for clinical depression symptoms, completed the SMS-PA-G and several other psychometric scales for capturing state mindfulness, self-efficacy, sense of coherence, anxiety, depression, and physical activity. We conducted reliability and item analyses and ran a confirmatory factor analysis. Also, we assessed construct validity through correlations with the abovementioned scales and through differences in SMS-PA scores between physically active and nonactive participants. Results: The mean SMS-PA-G score in our sample was 25.3 with a standard deviation of 8.5. The item and reliability analyses provided satisfactory Cronbach’s alpha and discriminatory power values. The confirmatory factor analysis showed that physical activity mindfulness can best be described via a bifactor model, with specific mind and body factors and a general mindfulness factor. We found the expected relationships with the attention subscale of state mindfulness, self-efficacy, and sense of coherence but did not find them with the awareness subscale of state mindfulness, depression, and anxiety. As hypothesised, physically active participants exhibited higher SMS-PA-G values than nonactive participants. Conclusions: The SMS-PA-G is an internally consistent test instrument that captures respondents’ general physical activity mindfulness and their attention to mental and bodily events. Whereas validity evidence was generally supportive of the SMS-PA-G, its relationships with other constructs require further investigation. Trial registration: ISRCTN, ISRCTN12347878. Registered 28 March 2022, https://www.isrctn.com/ISRCTN12347878.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Exercise; German; Mindfulness; Physical activity; State; Validation